PERLINDUNGAN HUKUM TERHADAP ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA - Muhammad Fachri Said (JCH (Jurnal Cendekia Hukum), 2018)
This study aims to analyze the problem of legal protection for children in the perspective of human rights. The type of this research is socio-juridical or including descriptive research with a non-doctrinal approach, which views law as a socio-empirical symptom observed in experience. The research method used is descriptive research with the type of incorporation of normative legal research with sociological legal research related to the implementation of legal protection for children in the perspective of human rights. The results of the study show that the results of this study are the legal protection of children in the perspective of human rights in essence is an effort made by parents, government and society to fulfill and guarantee all children's rights that have been guaranteed in the convention of children's rights and laws Number 35 of 2014 concerning Child Protection. Legal protection for children in the perspective of human rights is less implemented because the government has not implemented its obligations in fulfilling children's rights so that there are still legal violations of children. The recommendation of this research is to implement legal protection for children in the perspective of human rights, parents should be fully responsible for the behavior of children and the government establishes policies that are in line with the wishes of the community, so that the common perception between parents, government and society is realized in fulfilling the rights child.